Architectural work quality standard for BinaRaya Group PKINK / Muhammad Shahrin Safri - Safri, Muhammad Shahrin (Universiti Teknologi Mara, Perak, 2014)
Quality Standard in construction industry consists of three main work which are Structural work, Architectural work and Mechanical work. A quality construction project should be carry out by expertise project team in handling the quality standard assessment and should be applying in building work An Architect, Main Contractor, Quantity Surveyor, M&E Consultant and C&S Consultant should be take any Quality Standard Assessment for building work as their guidance to carry out any building work. Nowadays, this assessment is rarely use due to the attitude such as quickly going to be finished a project and to get more profit from a project. During the practical period in Kelantan where the site is specifically located in Rantau Panjang under the Binaraya PKINK company, the construction works are fully done through the structural work since the practical started. What is only left are finishing work and cleaning work. Thus, it is a constraint and limitation to develop the knowledge in construction.